2015
DOI: 10.1097/mib.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity Assessment in IBD

Abstract: C-reactive protein and fecal calprotectin are useful for the identification of endoscopically active IBD, but normal results do not confirm endoscopic remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(53 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…This appears to be a more clinically relevant comparison as the goal of IBD therapy is mucosal healing, which in turn is associated with durable remission and decreased risk of surgery [27]. Consistent with previous work [14, 15, 25], in our study, SIBDQ and HBI correlated poorly with endoscopic disease activity in CD. When examining the relationship between SIBDQ and endoscopic disease activity, Casellas et al [25] reported a correlation of −0.31, similar to the −0.17 in this study.…”
Section: Discussionsupporting
confidence: 89%
“…This appears to be a more clinically relevant comparison as the goal of IBD therapy is mucosal healing, which in turn is associated with durable remission and decreased risk of surgery [27]. Consistent with previous work [14, 15, 25], in our study, SIBDQ and HBI correlated poorly with endoscopic disease activity in CD. When examining the relationship between SIBDQ and endoscopic disease activity, Casellas et al [25] reported a correlation of −0.31, similar to the −0.17 in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Periodic monitoring is also necessary to avoid persistent chronic inflammation that can cause colorectal cancer. In addition to serum CRP, recent reports showed that faecal calprotectin was an effective biomarker for mucosal healing; 27 however, faecal samples have inherent associated problems such as limited quantitative capability and cumbersome sampling, which are not significant concerns for serum samples. Accurate detection of mucosal inflammation by a serum biomarker will facilitate the avoidance of frequent endoscopic procedures in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The current diagnosis and management of IBD is based on clinical and endoscopic criteria [ 29 ]. More specifically, as routine clinical assessment is often inaccurate with respect to endoscopic activity [ 30 ], colonoscopy represents the gold standard technique for the evaluation of disease severity. However, due to the complexity and invasiveness of this practice, there is a pressing need for new non-invasive biomarkers to improve disease activity detection, in order to better determine prognosis and to monitor drug response.…”
Section: Resultsmentioning
confidence: 99%